Effect of organic soil amendments against rice sheath blight - M. MUTHUSAMY, B. MEENA and (Indian Phytopathology, 2002)
Neem [Azadirachta indica] cake (at 150 kg/ha) was the most effective treatment in reducing disease incidence and severity caused by Rhizoctonia solani on rice, compared with the control. This was followed by farmyard manure and decomposed coir pith (both at 12.5 t/ha).